Shoreline Change Assessment in Varosha, Famagusta, Cyprus: A Case Study of a Ghost Town Using Aerial Photographs and Very High-Resolution Satellite Data (1963–2024) - C. Theocharidis; C. Theocharidis; M. Eliades; K. Themistocleous; K. Neocleous; C. Kontoes; D. Hadjimitsis; D. Hadjimitsis (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Understanding and managing shoreline dynamics is crucial for the sustainability of coastal ecosystems. The natural forces combined with human activities and climate change continuously reshape our coastlines. This study provides a comprehensive and spatial accurate analysis of shoreline change along the Varosha coastline in Cyprus, covering the period from 1963 to 2024. Forecasts for 2034 and 2044 were conducted using the Kalman filter. Using aerial photographs and Very High-Resolution (VHR) satellite imagery, historical shorelines were mapped, and the erosion and accretion rates were quantified using the ArcGIS Pro and the Digital Shoreline Analysis System (DSAS). The findings revealed considerable spatial variations along the 6.4 km of the studied coastline. The northern and southern sections showed predominant erosional trends, with maximum erosion rates of −0.29 m/year, while the central region exhibited accretion, with maximum accretion rates of 0.43 m/year. This research emphasises the importance of continuous coastal monitoring and advanced geospatial analysis to inform sustainable management strategies. This rare case study enhances our understanding of natural coastal processes due to the absence of human interventions.